Revitalisasi Posyandu untuk Meningkatkan Fungsi Layanan Kesehatan dan Edukasi Masyarakat di RW 04 Desa Tugumukti Kecamatan Cisarua Kabupaten Bandung Barat: Pengabdian - Annisa Yunda Amalia; Azka Jamilah Wardah; Azkia Zuhratul Maylafaiza; Djalalludin Akbar; Hadi Zidan Almughny; Indriatun Ainun Putri; Ni’mah Afiah Sholihah; Rd Ajeng Tedjaningrum; Talcha Khairunnisa Zaizafuun; Wanda Allya Sya’bania; Siti Aisyatul Mahmudah Badruzaman (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The role of Posyandu in community health services is not limited to child health care, immunization, and maternal health examinations, but also encompasses an educational function for the community. The success of Posyandu is determined by several key factors, including the availability of adequate facilities, a comfortable environment, and the continuity of health education activities. The revitalization of Posyandu in RW 04, Tugumukti Village, Cisarua District, West Bandung Regency was designed to improve the quality of health services and community education, with a particular emphasis on immunization and child development. The intervention was carried out over one month using the Participatory Action Research (PAR) methodology, which highlights the critical role of community involvement in all stages, including planning, implementation, monitoring, and reflection. Revitalization efforts were realized through infrastructure improvements such as repainting, the development of educational murals, installation of health-related posters and stickers, establishment of a child-friendly reading corner, and provision of handwashing facilities. The results of these activities showed significant improvements in comfort, aesthetic appeal, and community engagement. For example, the number of participants in the immunization outreach program increased from an average of 5 individuals before revitalization to 20 after implementation. The revitalization of Posyandu has demonstrated not only improvements in physical attributes but also enhanced community trust in community-based health services. Therefore, this program plays a vital role in strengthening the function of Posyandu as both a health service center and a platform for educational and community empowerment initiatives